Drót háttér archív
bombing of Budapest in World War II, war in Hungary I-II, archival footages, front, Soviet military cemetery, Russian langauge signs, river, 56.40-86.56 contemporary Russian language propaganda documentary, Malinovsky, 2nd Ukrainian front, the shooting of Ostapenko, Victory of the Red Army